Acceptability of Indigenous Philippine Berry [LIPOTE, Syzygium curranii (C.B. ROB.) MERR., MYRTACEAE] as an entrepreneurial product (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2005)
The study was designed to determine the acceptability of processed lipote as an entrepreneurial product based on appearance, palatability and general acceptability. The respondents consisted of 12 laboratory panelists (food technology students) and 100 consumers who were purposively chosen from the Cavite State University (CvSU) Home Economics and Vocational and Technical Education Department (HEVTED) population. Score sheets using a four-point Hedonic scale and a questionnaire were given to the respondents to gather the data. Age, gender, educational attainment, family income, food and entrepreneurial orientation were factors found to be correlated with acceptability. However, coefficients of correlation were weak to be predictive. There were significant differences in the perceived acceptability of processed lipote products between the two groups of respondents. All processed lipote products were found acceptable in terms of appearance, palatability and general acceptability. However, jelly was found to be more acceptable than jam and juice. Tertiary Home Economics curricula should incorporate product development using indigenous fruits as part of entrepreneurship to create more livelihood opportunities, thereby improving family well-being. The country's rich indigenous fruits should be brought to the fore, their uses, importance and abundance could provide researchers, policy makers, teachers and community leaders bases to enrich and enhance the young generations love for the country's natural resources.